Acute histoplasmosis in travelers: a retrospective study in an Italian referral center for tropical diseases. (2nd January 2020) - Staffolani, Silvia; Riccardi, Niccolò; Farina, Claudio; Lo Cascio, Giuliana; Gulletta, Maurizio; Gobbi, Federico; Rodari, Paola; Ursini, Tamara; Bertoli, Giulia; Ronzoni, Niccolò; Bisoffi, Zeno; Angheben, Andrea
ABSTRACT: Purpose : Histoplasmosis is a fungal infection acquired through inhalation of Histoplasma capsulatum microconidia, mostly present in the Americas. Both immunocompetent and immunocompromised patients can present a wide spectrum of signs/symptoms, ranging from mild disease to a severe, disseminated infection. The aim of this observational study is to describe histoplasmosis cases diagnosed in travelers and their clinical/radiological and therapeutic pattern. Methods : Retrospective study at the Department of Infectious – Tropical Diseases and Microbiology (DITM) of Negrar, Verona, Italy, between January 2005 and December 2015. Results : Twenty-three cases of acute histoplasmosis were diagnosed, 17 of which belong to the same cluster. Seven of the 23 patients (30.4%) were admitted to hospital, four of whom underwent invasive diagnostic procedures. Thirteen patients (56.5%) received oral itraconazole. All patients recovered, although nine (39.1%) had radiological persisting lung nodules at 12 month follow up. Conclusions : Clinical, laboratory and radiological features of histoplasmosis can mimic other conditions, resulting in unnecessary invasive diagnostic procedures. However, a history of travel to endemic areas and of exposure to risk factors (such as visits to caves and presence of bats) should trigger the clinical suspicion of histoplasmosis. Treatment may be indicated in severe or prolonged disease.